Literacy instruction for English language learners, Pre-K-2 - Barone, Diane M.; Xu, Shelley Hong, 1964- (Solving problems in the teaching of literacy., 2008)
Summarizing current research and weaving it into practical instructional strategies that teachers can immediately use with young English language learners (ELLs), this book addresses a major priority for today's primary-grade classrooms. All aspects of effective instruction for ELLs are explored: oral language development and instruction, materials, word study, vocabulary, comprehension, writing, and home-school connections. Assessment is discussed throughout, and is also covered in a separate chapter. The volume is packed with realistic examples, lesson planning ideas, book lists, online resources, and reproducibles. Discussion and reflection questions enhance its utility as a professional development tool or course text. - Publisher.